Performance evaluation of various link quality metrics using cross layer routing for wireless multimedia sensor networks. (7th May 2019) - Aswale, Shailendra; Ghorpade, Vijay R.
For the past few years, link quality estimation has been an active area of research in wireless networks. Low-power wireless links are error-prone, asymmetric and unreliable in nature. Therefore, understanding the behaviour and characteristics of low-power radio links is essential to design effective and efficient routing protocol in wireless networks. The objective of this paper is to estimate and evaluate the quality of a link with single link quality metric and amalgamated link quality metric. In addition, these estimated link quality metrics are respectively used in a generic routing cost function of the proposed link quality-based cross layer routing (LQCLR) protocol. Extensive simulation results are presented, which give insights on how estimated link quality with single and amalgamated link quality metrics affects the performance of routing protocol in wireless multimedia sensor network (WMSN).